2022
DOI: 10.1186/s13007-022-00899-7
|View full text |Cite
|
Sign up to set email alerts
|

Wheat leaf area index prediction using data fusion based on high-resolution unmanned aerial vehicle imagery

Abstract: Background Leaf Area Index (LAI) is half of the amount of leaf area per unit horizontal ground surface area. Consequently, accurate vegetation extraction in remote sensing imagery is critical for LAI estimation. However, most studies do not fully exploit the advantages of Unmanned Aerial Vehicle (UAV) imagery with high spatial resolution, such as not removing the background (soil and shadow, etc.). Furthermore, the advancement of multi-sensor synchronous observation and integration technology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 69 publications
4
11
0
Order By: Relevance
“…The RF model performed better than the SVR model in the three machine learning models, while the BP model was the weakest in all three types of data inputs. This was consistent with the view of Wu et al (2022), who used random forest, support vector machine and multiple linear regression techniques to fuse spectral, structural and thermal characteristics of the canopy to estimate LAI in wheat, and revealed that regardless of which features were fused, RF performed best in LAI prediction. Zha et al (2020) also found that RF was superior to SVR, MLR and ANN in predicting nitrogen content in rice using spectral features.…”
Section: Estimation Of Lai and Lcc By Fusion Of Preparation Indices A...supporting
confidence: 87%
See 2 more Smart Citations
“…The RF model performed better than the SVR model in the three machine learning models, while the BP model was the weakest in all three types of data inputs. This was consistent with the view of Wu et al (2022), who used random forest, support vector machine and multiple linear regression techniques to fuse spectral, structural and thermal characteristics of the canopy to estimate LAI in wheat, and revealed that regardless of which features were fused, RF performed best in LAI prediction. Zha et al (2020) also found that RF was superior to SVR, MLR and ANN in predicting nitrogen content in rice using spectral features.…”
Section: Estimation Of Lai and Lcc By Fusion Of Preparation Indices A...supporting
confidence: 87%
“…Unmanned Aerial Vehicle (UAV) remote sensing has rapidly evolved into a crucial tool for agricultural monitoring, driven by its advantages of low cost, high flexibility, and the ability to acquire high temporal and spatial resolution data on demand (Lan et al, 2020;Yan et al, 2019;Yang et al, 2023). Various remote sensing data, including hyperspectral, multispectral, and thermal infrared, are widely used for estimating crop parameters such as leaf area index (Liang et al, 2015;Roth and Streit, 2018;Wu et al, 2022), leaf chlorophyll content (Borhan et al, 2004;Daughtry et al, 2000;Jena, 2017), above-ground biomass (Eckert, 2012;Liu et al, 2019;, and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This advantage guarantees additional information for data fusion with the vegetation indices as full explanations. According to Wu et al [26], the combination of UAV-based multi-sensor synchronous observation data products can bring higher accuracy in the prediction process.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, small-sized unmanned aerial vehicles (UAVs) brought the capability to acquire remote-sensed data from different sensors with high spatial resolution and good temporal flexibility [22]. Studies were performed using UAV-based imagery to correlate the LAI in vineyards [10,[23][24][25][26], olives [27], wheat [28], maize [29,30], mangrove forests [15], and rice [31,32].…”
Section: Introductionmentioning
confidence: 99%